2017
DOI: 10.1038/s41598-017-11302-0
|View full text |Cite
|
Sign up to set email alerts
|

New compounds identified through in silico approaches reduce the α-synuclein expression by inhibiting prolyl oligopeptidase in vitro

Abstract: Prolyl oligopeptidase (POP) is a serine protease that is responsible for the maturation and degradation of short neuropeptides and peptide hormones. The inhibition of POP has been demonstrated in the treatment of α-synucleinopathies and several neurological conditions. Therefore, ligand-based and structure-based pharmacophore models were generated and validated in order to identify potent POP inhibitors. Pharmacophore-based and docking-based virtual screening of a drug-like database resulted in 20 compounds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
(70 reference statements)
1
29
0
Order By: Relevance
“…Therefore, we argued that the resultant pharmacophore is a suitable choice to use as a 3D query in virtual screening of the drug-like database for the identification of candidate inhibitors of Cdk5. The selected pharmacophore obtained highest GH and EF scores of 0.88 and 7.23, respectively, which validates its suitability in virtual screening practices [ 34 , 35 ]. Since, drug-like molecules are restricted to certain chemical properties such as physiochemical and pharmacokinetics and pharmacodynamics properties.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Therefore, we argued that the resultant pharmacophore is a suitable choice to use as a 3D query in virtual screening of the drug-like database for the identification of candidate inhibitors of Cdk5. The selected pharmacophore obtained highest GH and EF scores of 0.88 and 7.23, respectively, which validates its suitability in virtual screening practices [ 34 , 35 ]. Since, drug-like molecules are restricted to certain chemical properties such as physiochemical and pharmacokinetics and pharmacodynamics properties.…”
Section: Discussionmentioning
confidence: 56%
“…Since, molecular docking does not provide simulated physiological environment and real-time behavior of the drug-receptor interaction; therefore, molecular dynamics (MD) simulation was employed to identify the true positive inhibitors of Cdk5/p25 [ 35 , 36 , 58 ]. The root mean square deviation (rmsd) analysis is a key factor to evaluate the stability and successful execution of MD simulation [ 34 , 35 , 58 ]. Our results suggested that the final candidate inhibitors showed stable rmsd of the alpha carbon atoms (C α ) of Cdk5/p25, the backbone atoms of Cdk5/p25, and the Cdk5/p25 in complex with candidate inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with PREP have shown beneficial effects on aSyn aggregation and clearance after PREP inhibitor treatment 16 18 , 44 , 53 . However, information about aSyn toxicity in the total absence of PREP has not been reported.…”
Section: Discussionmentioning
confidence: 99%